Analisis Yuridis Keabsahan Penyelenggaraan Rapat Umum Pemegang Saham (Rups) Secara Online Untuk Mewujudkan Kepastian Hukum (Studi Penelitian PT Midi Utama Indonesia Tbk (Midi)) - Chandra, Fernando; Erniyanti, Erniyanti; Fadlan, Fadlan; Respationo, Soerya (Universitas Ekasakti, 2023)
The development of information and communication technology has had a significant impact on various aspects of life, including the business world. One form of this development is the use of a digital platform to hold an online General Meeting of Shareholders (GMS), this is what PT Midi Utama Indonesia Tbk (MIDI) is doing, with a special focus on harmonizing the holding of the online GMS with Article 77 of the Law Limited Liability Company and comparison with Article 16 paragraph (1) of the Law on Notary Positions. This research has three problem formulations, namely regarding legal regulations related to the legality of holding an online General Meeting of Shareholders (GMS) to create legal certainty, implementation of the legality of holding an online General Meeting of Shareholders (GMS) to create legal certainty, and factors that become obstacles. and obstacles and solutions in implementing the validity of holding an online General Meeting of Shareholders (GMS). This research uses normative juridical legal research methods and sociological or empirical legal research. This normative juridical research is carried out by examining library materials or secondary data. The data used in this research are primary data and secondary data. Primary data in this research is in the form of interviews and observations, while secondary data used in this research consists of primary legal materials, secondary legal materials and tertiary legal materials. The results of this research are that the implementation of Online GMS is permitted according to legal regulations based on Article 76 Jo. Article 77 of the Limited Liability Company Law and POJK Number 16/POJK.04/2020. Basically, the implementation of an online GMS does not violate the law and remains legal. In its implementation carried out by a Notary, the preparation of a GMS deed carried out online is still difficult to implement firmly, because there is still uncertainty regarding the Notary's authority. Obstacles that can occur are related to the mechanism for holding an online GMS, because this GMS is carried out online, the main obstacle or obstacle is located in the network or computer equipment.